Discrepancy between Regulation and Reality: An Analysis of the Implementation of the Merdeka Curriculum in English Learning at Elementary School - Mutia Rahmi; Hajjah Rafiah; Nonong Rahimah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: English is an important subject to teach at the primary school level because students are in the golden age, a critical period for developing language abilities. In the Merdeka Curriculum, English is provided as an elective subject for two lesson hours per week. However, problems were found at West Kelayan 3 Elementary School, including students' low English proficiency, and the teacher's lack of understanding of Curriculum Merdeka-based learning in planning, implementation, and evaluation. Aim: This research aims to describe the implementation of English learning based on the Curriculum Merdeka at West Kelayan 3 Elementary School. Method: This research used a qualitative descriptive method. The data sources were the principal, the English teacher, and grade IV students of West Kelayan 3 Elementary School. Data were collected through observation, interviews, and documentation, then analyzed descriptively to make conclusions. Result and Discussion: The results of this research indicate that Curriculum Merdeka-based English learning consists the following aspects: (1) teachers prepare the Learning Objective Flow (ATP) and lesson plans adapted from the internet and books; (2) learning implementation consists three stages, introduction, core activities, and closing using lecture method and drill method; (3) Evaluation is conducted at the end of the learning process. The learning tools used include student worksheets developed by the teacher or adapted from books. Remedial activities are provided for students who have not achieved the minimum level of learning mastery. Conclusion: Based on the results of this research and the discussion on the implementation of Merdeka Curriculum-based English Learning in grade IV at West Kelayan 3 Elementary School, it can be concluded that the learning process has been implemented through several systematic stages. In the planning stage, teachers prepare lesson plans obtained from the internet and adapt them to students' needs